TRANSFORMING CUSTOMER EXPERIENCES: CRM'S INFLUENCE IN JORDANIAN TELECOM - Al-Mansoori, Sarah Ahmed; Al-Haddad, Mohammad Khalid (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This paper underscores the paramount importance of prioritizing the customer within corporate paradigms. The conversion of customer desires and needs into standardized production benchmarks is pivotal for success in the business landscape. The absence of these standards in product development invariably leads to failure, underscoring the indispensability of adhering to purchase specifications. To secure and augment customer bases, corporations are engrossed in not only establishing interactive customer relationships but also fortifying these associations through specialized tools and strategies tailored for cultivating enduring customer bonds. Amidst escalating competition and declining customer satisfaction, the role of Customer Relationship Management (CRM) has evolved significantly. This evolution is necessitated by imperatives such as bolstering service quality to cultivate trust, enhancing customer satisfaction, engendering loyalty, and heightening retention rates. By mitigating the competitive impact, enterprises can achieve a twofold objective of sustaining customer loyalty and fostering resilience in the market landscape